Development of Clinical-Stage Human Monoclonal Antibodies That Treat Advanced Ebola Virus Disease in Nonhuman Primates. (31st May 2018) - Pascal, Kristen E; Dudgeon, Drew; Trefry, John C; Anantpadma, Manu; Sakurai, Yasuteru; Murin, Charles D; Turner, Hannah L; Fairhurst, Jeanette; Torres, Marcela; Rafique, Ashique; Yan, Ying; Badithe, Ashok; et al.
Abstract: Background: For most classes of drugs, rapid development of therapeutics to treat emerging infections is challenged by the timelines needed to identify compounds with the desired efficacy, safety, and pharmacokinetic profiles. Fully human monoclonal antibodies (mAbs) provide an attractive method to overcome many of these hurdles to rapidly produce therapeutics for emerging diseases. Methods: In this study, we deployed a platform to generate, test, and develop fully human antibodies to Zaire ebolavirus . We obtained specific anti-Ebola virus (EBOV) antibodies by immunizing VelocImmune mice that use human immunoglobulin variable regions in their humoral responses. Results: Of the antibody clones isolated, 3 were selected as best at neutralizing EBOV and triggering FcγRIIIa. Binding studies and negative-stain electron microscopy revealed that the 3 selected antibodies bind to non-overlapping epitopes, including a potentially new protective epitope not targeted by other antibody-based treatments. When combined, a single dose of a cocktail of the 3 antibodies protected nonhuman primates (NHPs) from EBOV disease even after disease symptoms were apparent. Conclusions: This antibody cocktail provides complementary mechanisms of actions, incorporates novel specificities, and demonstrates high-level postexposure protection from lethal EBOV disease in NHPs. It is now undergoing testing in normal healthy volunteers in preparation for potential use in future Ebola epidemics.